Stakeholders’ assessment of deviant behaviour among adolescents in Ibadan Southwest Local Government Area of Oyo State (2024)
This study examined the perceived factors that influenced deviant behaviour among adolescents, its effects and ways to combat them, in Ibadan South-west local government area, Oyo State. The sequential mixed methods (QUAN+qual) design was adopted. The multi-stage sampling procedure was adopted. The information pertaining to this study was collected from the teachers, administrators, parents, community leaders and religious leaders. Instruments used for the study were Stakeholders’ Rating of the Precipitating Factors Predisposing Deviant Behaviour (r= 0.81); Perception of the Prevalence of Deviant Behaviour (r=0.72) while In-depth Interviews were conducted to collect data. The quantitative data were analysed using descriptive statistics, while the qualitative data were content analysed. Findings revealed that “Street criminality”, “Cyber deviance” and “Juvenile delinquency” were ranked top three deviant behaviours among adolescents. Also, results show that “Family instability”, “Economic hardship” and “Media influence” were ranked top three factors driving deviant behaviour among adolescents. The qualitative analysis revealed gambling, risky sexual behaviour, substance abuse, flagrant abuse of rules and regulations, poor academic performance, high-handedness, and criminality as the effects of deviant behaviour, while challenges are faced in curbing deviant behaviour among adolescents in the society. It is recommended that parents and guardians should always keep a close watch on the activities of their children/wards at all-time especially at tender age with the aim of curbing any negative behaviour found in them at any point in time. Parents should encourage strong bond in love and avoid violence and using abusive words in the presence of their children.